Determinants of outcome following laparoscopic peritoneal lavage for perforated diverticulitis. Issue 12 (9th September 2014) - Radé, F; Bretagnol, F; Auguste, M; Di Guisto, C; Huten, N; de Calan, L
Abstract: Background: Laparoscopic peritoneal lavage has been proposed for generalized peritonitis from perforated diverticulitis to avoid a stoma. Reports of its feasibility and safety are promising. This study aimed to establish determinants of failure to enable improved selection of patients for this approach. Methods: The study included all patients with perforated sigmoid diverticulitis who underwent emergency laparoscopic peritoneal lavage from January 2000 to December 2013. Factors predicting failure of laparoscopic treatment were analysed from data collected retrospectively. Results: For patients undergoing emergency sigmoid resection (72 of 361), mortality and morbidity rates were 13 and 35 per cent respectively. In all, 71 patients had laparoscopic lavage, with mortality and morbidity rates of 6 and 28 per cent respectively. Reintervention was necessary in 11 patients (15 per cent) for unresolved sepsis. Age 80 years or more, American Society of Anesthesiologists grade III or above, and immunosuppression were associated with reintervention. Conclusion: Elderly patients and those with immunosuppression or severe systemic co-morbidity are at risk of reintervention after laparoscopic lavage. Abstract : Defines patients at risk of reintervention